Optimization of Resonant Arrays for Dynamic Wireless Power Transfer Using Adaptive Termination - Joao Dinis; Jose Alberto; Antonio J. Marques Cardoso (IEEE Open Journal of the Industrial Electronics Society)
This article introduces the implementation of an adaptive termination impedance alongside a corresponding control algorithm designed for resonant arrays in inductive wireless power transfer systems for vehicle charging applications. The integration of an adaptive termination impedance in the final cell of the array significantly improves both energy transfer between the transmitter array and the receiver. By employing the proposed algorithm, which estimates the receiver’s position relative to the array through voltage and current measurement in the first cell directly connected to the power source, the need for additional position sensors is eliminated. Moreover, this innovative approach not only reduces the number of components but also lowers system cost and complexity, while allowing the system to be modular, as the proposed method works for any number of array cells. The effectiveness of the proposed solution has been validated through comprehensive simulations and experimental testing.